Tumor immune microenvironment of primary prostate cancer with and without germline mutations in homologous recombination repair genes. Issue 6 (28th June 2022) - Trigos, Anna Sofia; Pasam, Anupama; Banks, Patricia; Wallace, Roslyn; Guo, Christina; Keam, Simon; Thorne, Heather; ,; Mitchell, Catherine; Lade, Stephen; Clouston, David; Hakansson, Alexander; et al.
Abstract : Background: Aberrations in homologous recombination repair (HRR) genes are emerging as important biomarkers for personalized treatment in prostate cancer (PCa). HRR deficiency (HRD) could affect the tumor immune microenvironment (TIME), potentially contributing to differential responses to poly ADP-ribose polymerase (PARP) inhibitors and immune checkpoint inhibitors. Spatial distribution of immune cells in a range of cancers identifies novel disease subtypes and is related to prognosis. In this study we aimed to determine the differences in the TIME of PCa with and without germline ( g ) HRR mutations. Methods: We performed gene expression analysis, multiplex immunohistochemistry of T and B cells and quantitative spatial analysis of PCa samples from 36 patients with g HRD and 26 patients with sporadic PCa. Samples were archival tumor tissue from radical prostatectomies with the exception of one biopsy. Results were validated in several independent cohorts. Results: Although the composition of the T cell and B cells was similar in the tumor areas of g HRD-mutated and sporadic tumors, the spatial profiles differed between these cohorts. We describe two T-cell spatial profiles across primary PCa, a clustered immune spatial (CIS) profile characterized by dense clusters of CD4 + T cells closely interacting with PD-L1 + cells, and a free immune spatial (FIS) profile of CD8 + cells in close proximity to tumor cells. g HRD tumors had a more T-cell inflamed microenvironment than sporadic tumors. The CIS profile was mainly observed in sporadic tumors, whereas a FIS profile was enriched in g HRD tumors. A FIS profile was associated with lower Gleason scores, smaller tumors and longer time to biochemical recurrence and metastasis. Conclusions: g HRD-mutated tumors have a distinct immune microenvironment compared with sporadic tumors. Spatial profiling of T-cells provides additional information beyond T-cell density and is associated with time to biochemical recurrence, time to metastasis, tumor size and Gleason scores.